The Role of Blockchain Technology in Enhancing Financial Security amidst Digital Transformation - Yerram, Sridhar Reddy; Goda, Dileep Reddy; Mahadasa, Ravikiran; Mallipeddi, Suman Reddy; Varghese, Aleena; Ande, Janaki Rama Phanendra Kumar; Surarapu, Pavani; Dekkati, Sreekanth (Asian Business Review, 2021)
Amid the digital revolution, this study explores how blockchain technology can improve financial security. The primary goals are to examine how blockchain technology reduces cyber threats in the financial industry, evaluate regulatory factors that should be considered before adopting blockchain, and investigate the prospects for blockchain going forward. A review process based on secondary data is utilized, referencing academic articles, reports, and regulatory documents. Significant discoveries show that blockchain provides creative ways to reduce cyber threats, improve transparency, and foster financial transaction confidence. Nevertheless, issues, including adoption obstacles, regulatory uncertainties, and technological restrictions, must be resolved to reach their full potential. The policy implications indicate that stakeholders must collaborate, do continuous research, and establish clear regulatory frameworks to promote responsible blockchain adoption in the finance industry. Blockchain technology can transform financial security and encourage creativity in the digital world.